Clinicopathological evaluation of thyroid swelling in patient attending Hamidia Hospital Bhopal - Shukla, Samir; Tiwari, Shashi kant (International Surgery Journal, 2020)
Background: The prevalence of thyroid nodule ranges from 4-10% in general population. Its treatment includes either conservative management or surgical excision of gland. Fine needle aspiration cytology (FNAC) has emerged as most accepted, accurate diagnostic procedure and considered the gold standard diagnostic test in evaluation of thyroid nodule, other tests like ultrasound, nuclear scan used in conjunction with FNAC. The aim of study was to study the spectrum of diseases in thyroid swelling and accuracy of FNAC in the diagnosis. Methods: A prospective study, with total 50 patients, was conducted during period from 2017-2019 in department of surgery, Gandhi Medical College Bhopal. All patients who underwent thyroid surgeries were selected for study. All patients underwent detailed history, clinical examination, routine investigations, thyroid function test, FNAC, ultrasonography neck and histopathological examination. Results: Of 50 cases female to male ratio was 9.2:1, with median age group was 38.6 years. Among all, 42 (84%) were benign, 3 (6%) malignant and 5 (10%) suspicious. Of 5 suspicious lesions, only 1 (5%) case found malignant. Hemi thyroidectomy was common surgery performed, followed by subtotal/near total and total thyroidectomy. Conclusions: Thyroid swellings are common in females occur in 3rd and 4th decade most commonly. FNAC is very useful and indispensable in the diagnosis. Most common non neoplastic and neoplastic lesion was solitary thyroid nodule and papillary carcinoma respectively.